Emerging Asia : changes and challenges (Asian Development Bank, 1997)
Asia is in the midst of a great economic and social transformation. In virtually every dimension, life in Asia is changing at an unprecedented pace: its people have become richer, healthier, better fed, and more educated in a remarkably short period of time. But not all Asians have benefited equally. Some countries, regions within countries, and groups within societies still lag seriously behind. Asia is also a much more polluted and environmentally degraded place than it was 30 years ago. This book, Emerging Asia: Changes and Challenges, looks at this great transformation and analyzes the prospects for its continuation. Taking a forward-looking and broad view of the development process, the book identifies the major trends that are likely to influence Asia's future. It then asks how these might affect future policy and institutional choices.